Associations of objectively measured physical activity and sleep in preschoolers aged 3 to 6 years - Miller, Laura; Dockrill, Mya; Corkum, Penny V.; Kirk, Sara F. L.; Stone, Michelle (Frontiers in Sleep, 2024)
Research has demonstrated various negative effects of poor sleep on overall health in children. Engaging in physical activity during the day is often recommended to help children sleep better. Limited research has examined this recommendation for preschool children, although physical activity is generally supported as a healthy sleep practice. When measuring physical activity and sleep, objective measures (e.g., accelerometers) are recommended as opposed to subjective measures (e.g., parental reports). The purpose of the current study was to examine the relationship between objectively measured sleep (key variables included sleep efficiency, sleep onset latency, and sleep duration) and physical activity (operationalized as mean daily total physical activity) among preschool-aged children in Nova Scotia, Canada. Children (n = 29) wore a wrist accelerometer to objectively measure sleep and wore an accelerometer on their waist to measure physical activity for nine consecutive days. Overall, linear regression analyses demonstrate physical activity as a predictor of sleep efficiency but not total sleep time or sleep onset latency among preschool-aged children. Future research should examine the causal relationships between sleep efficiency and physical activity by conducting interventions to increase physical activity and determining the impact on sleep efficiency.